Finding perfect - Mallery, Susan (Don Mills, Ont. : HQN, 2010)
When her best friend dies, leaving her three frozen embryos, Pia O'Brian decides to become a single mother, but fate has other plans for her when she runs into Raoul Moreno on her way to the clinic.
Keywords: Female friendship -- Fiction; Single mothers -- Fiction; Man-woman relationships -- Fiction; Love stories